ChemInform Abstract: Nickel‐Catalyzed Bis‐Allylation of Activated Nucleophiles with Allyl Alcohol. Issue 27 (16th June 2016) - Blieck, Remi; Azizi, Mohamed Salah; Mifleur, Alexis; Roger, Maxime; Persyn, Clement; Sauthier, Mathieu; Bonin, Helene
Abstract: Different combinations which contain a Ni compound are tested and the reaction is found to be best promoted by the Ni(cod)2 /dppb system.